"Matching" consent to purpose: The example of the Matchmaker Exchange. Issue 10 (12th July 2017) - Dyke, Stephanie O. M.; Knoppers, Bartha M.; Hamosh, Ada; Firth, Helen V.; Hurles, Matthew; Brudno, Michael; Boycott, Kym M.; Philippakis, Anthony A.; Rehm, Heidi L.
Abstract : The Matchmaker Exchange (MME) connects rare disease clinicians and researchers to facilitate the sharing of data from undiagnosed patients for the purpose of novel gene discovery. In this Commentary, we discuss consent considerations for data sharing in MME, which included both the ethical and legal differences between clinical and research settings and the level of privacy risk involved in sharing varying amounts of rare disease patient data to enable patient matches. Abstract: The Matchmaker Exchange (MME) connects rare disease clinicians and researchers to facilitate the sharing of data from undiagnosed patients for the purpose of novel gene discovery. Such sharing raises the odds that two or more similar patients with candidate genes in common may be found, thereby allowing their condition to be more readily studied and understood. Consent considerations for data sharing in MME included both the ethical and legal differences between clinical and research settings and the level of privacy risk involved in sharing varying amounts of rare disease patient data to enable patient matches. In this commentary, we discuss these consent considerations and the resulting MME Consent Policy as they may be relevant to other international data sharing initiatives.